Cohomological tensor functors on representations of the general linear supergroup - Heidersdorf, Thorsten; Weissauer, Rainer (Memoirs of the American Mathematical Society, 2021)
Cover -- Title page -- Chapter 1. Introduction -- Chapter 2. Cohomological Tensor Functors -- 2.1. The superlinear groups -- 2.2. The Duflo-Serganova functor -- 2.3. Cohomology functors -- 2.4. Support varieties and the kernel of -- 2.5. The tensor functor -- 2.6. The relation between ( ) and ( ) -- 2.7. Hodge decomposition -- 2.8. The case &gt -- 1 -- 2.9. Boundary maps -- 2.10. Highest weight modules -- 2.11. The Casimir -- Chapter 3. The Main Theorem and its Proof -- 3.1. The language of Brundan and Stroppel -- 3.2. On segments, sectors and plots -- 3.3. Mixed tensors and ground states -- 3.4. Sign normalizations -- 3.5. The main theorem -- 3.6. Strategy of the proof -- 3.7. Modules of Loewy length 3 -- 3.8. Inductive Control over -- 3.9. Moves -- Chapter 4. Consequences of the Main Theorem -- 4.1. Tannaka Duals -- 4.2. Cohomology I -- 4.3. Cohomology II -- 4.4. Cohomology III -- 4.5. The forest formula -- 4.6. -module structure on the cohomology ^{∙}_{ _{ }} -- 4.7. Primitive elements of ^{∙}_{ _{ }}( (1)) -- 4.8. Kac module of 1 -- 4.9. Strict morphisms -- 4.10. The module (( )ⁿ) -- 4.11. The basic hook representations -- Bibliography -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Kohomologieoperation; Allgemeine lineare Gruppe